Quality Control of Nitrogen Multiple Breath Washout in a Multicenter Pediatric Asthma Study - Nitsche, Catharina; Frauchiger, Bettina Sarah; Thiele, Dominik; Oestreich, Marc-Alexander; Husstedt, Berrit Liselotte; Grychtol, Ruth Margarethe; Maison, Nicole; Foth, Svenja; Meyer, Meike; Jakobs, Nikolas; Bahmer, Thomas; Hansen, Gesine; von Mutius, Erika; Kopp, Matthias (Klinische Pädiatrie, 2023)
Background Nitrogen multiple breath washout (N2MBW) is a lung function test increasingly used in small airway diseases. Quality criteria have not yet been globally implemented and time-consuming retrospective overreading is necessary. Little data has been published on children with recurrent wheeze or asthma from multicentered studies.Methods Children with wheeze or asthma and healthy controls were included in the longitudinal All Age Asthma Cohort (ALLIANCE). To assess ventilation inhomogeneity, N2MBW tests were performed in five centers from 2013 until 2020. All N2MBW tests were centrally overread by one center. Multiple washout procedures (trials) at the visit concluded to one test occasion. Tests were accepted if trials were technically sound (started correctly, terminated correctly, no leak, regular breathing pattern) and repeatable within one test occasion. Signal misalignment was retrospectively corrected. Factors that may impact test quality were analyzed, such as experience level.Results N2MBW tests of n=561 participants were analyzed leading to n=949 (68.3%) valid tests of n=1,390 in total. Inter-center test acceptability ranged from 27.6% to 77.8%. End-of-test criterion and leak were identified to be the most common reasons for rejection. Data loss and uncorrectable signal misalignment led to rejection of 58% of trials in one center. In preschool children, significant improvement of test acceptability was found longitudinally (χ2(8)=18.6; p=0.02).Conclusion N2MBW is feasible in a multicenter asthma study in children. However, the quality of this time-consuming procedure is dependent on experience level of staff in preschool children and still requires retrospective overreading for all age groups.
Keywords: N2MBW; MBW; lung function; ventilation inhomogeneity; LCI; Turn Over